Peasants and agricultural wageworkers in Argentina in the 20th – 21st centuries: Some paradoxes of the dichotomy ‘rural–urban’ - Crovetto, Maria Marcela (2023)
The article proposes an unusual starting point to consider the peasantry in Argentina — the concept of rurality. This paper is based on the already highly debated conceptualizations of the rural–urban question in dichotomous terms; the author develops an analytical approach that implies a complex perspective of spatiality in non-binary forms. Such a task involves the integration of other variables in the study of societies connected with the agrarian worlds, already stripped of obsolete univocal characteristics. To solve this task, the author revises some of the discussions of peasant decomposition and wage earning in Argentina. These debates have renewed the understanding of the present peasant and agricultural wage-earning in Argentina, given that historically there were only peasants in the ‘non-pampean’ area (outside the Pampas region). It was not until the 1960 that the peasant self-perceptions and organizations emerged under the slowing demand for labor in the industrial sector. After the analysis of documentary sources in various regions of the country, the author argues that there are rural workers of non-peasant origin, which can be empirically proved. They depend on subsistence activities with the classic peasant features. Agricultural workers and inhabitants of rural worlds are not necessarily the same subjects mobilized daily and being the result of the agro-industrial activities since the 1980s. Since then, they have acquired typical characteristics of the globalized capitalist mode of production. Thus, paradoxically, in the transition from the 20th to the 21st century, in some regions of Argentina globalization creates the peasantry.